Laser-assisted robotic roller forming of an ultrahigh strength martensitic steel. (October 2022) - Liu, Yi; Min, Junying; Zhang, Jun; Cai, Wayne; Carlson, Blair E.; Bobel, Andrew C.; Hector, Louis G.; Sachdev, Anil K.
Abstract: Laser-assisted robotic roller forming (LRRF) was developed as a means for bending ultrahigh strength martensitic steel (MS1300) strip without fracture. The strip is bent through application of a thermal load from a fiber laser followed by a mechanical load from a steel roller: the translational motion of both is controlled via an industrial robot. A combined experimental and computational methodology was developed using a lab-scale LRRF cell and a finite element (FE) model that accounts for thermo-elastic-plastic bending from laser irradiation and the roller contact. The FE model was calibrated according to the experimental temperature data to reconstruct the spatiotemporal temperature field. The simulated temperature field was further applied to analyze MS1300 microstructure evolution and microhardness distribution. It is shown that the material under the laser beam was austenitized and then quickly cooled down. The microstructure in the bend subsequently consisted of new martensite near the tension (irradiated) surface, a through-thickness region consisting of both martensite and tempered martensite, and tempered martensite at the compression side of the bend.